?EVALUATION OF SHALLOW GROUNDWATER QUALITY IN URBA~ AREAS OF KARACHI (PAKISTAN)-INORGANIC NUTRIENTS AND BACTERIAL CONTAMINATION - Zubair, Arif; Rippey, Brian (Biological Sciences - PJSIR, 2000)
A total of 193 groundwater samples, collected from Karachi-urban areas, were analysed to determine the concentrations of nitrate, nitrite, ammonia andbacterial densities (coliformand faecalcoliformbacteria). From nitrogen component view point groundwater quality ofKarachi isacceptablefor humanconsumption. However.coliform bacteria were higherin 83% samples than the WHO permissiblelimit.The inorganic nitrogen andbacteriologicalcontamination levels suggest that the groundwater quality is mainly affected by wastewater.